2022
DOI: 10.4103/jispcd.jispcd_65_22
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Current Evidence on the Use of Oral Antiseptics Against SARS-CoV-2

Abstract: A BSTRACT Aims and Objectives: The detection of SARS-COV-2 in the oral cavity has generated endless claims about the efficacy of using oral mouthwashes to reduce viral load. This review aims to assess the current evidence on the use of oral antiseptics against SARS-CoV-2 and to assess the certainty of the evidence according to the GRADE system. The question this study focussed on was what is the efficacy of oral antiseptics against SARS-CoV-2? Materials an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Treatment with oral antiseptics has been shown to contribute to eliminating SARS-CoV-2 from the O.C. by some preliminary clinical evidence [172,173]. The most effective oral antiseptics against SARS-CoV-2 are, in fact, povidone-iodine, hydrogen peroxide, and cetylpyridinium chloride, which were shown to reduce viral load in COVID-19 patients' saliva 2-4 h after mouthwashing [173,174].…”
Section: Therapeutic Potential Of Oc Against Sars-cov-2mentioning
confidence: 99%
“…Treatment with oral antiseptics has been shown to contribute to eliminating SARS-CoV-2 from the O.C. by some preliminary clinical evidence [172,173]. The most effective oral antiseptics against SARS-CoV-2 are, in fact, povidone-iodine, hydrogen peroxide, and cetylpyridinium chloride, which were shown to reduce viral load in COVID-19 patients' saliva 2-4 h after mouthwashing [173,174].…”
Section: Therapeutic Potential Of Oc Against Sars-cov-2mentioning
confidence: 99%
“…This includes household and healthcare settings that perform aerosol-generating procedures. Virucidal effects have been seen in substances contained in oral antiseptics [ 13 , 14 , 15 ]. Interestingly, animal models observing SARS-CoV-1, a virus similar in genomics to SARS-CoV-2, showed that the virus persisted in oral mucous membranes for up to 2 days before infecting the lower respiratory tract [ 16 ].…”
Section: Introductionmentioning
confidence: 99%